Applied data visualization with R and ggplot2 : Create useful, elaborate, and visually appealing plots - Moulik, Tania (Packt Publishing Ltd, 2018)
When data is presented to you in a graphical or pictorial format, you can analyze it more effectively. This book begins by introducing you to basic concepts, such as grammar of graphics and geometric objects. It then goes on to explain these concepts in detail with examples. Once you are comfortable with basics, you can learn all about the ...